Effect of Artificial Insemination on different production parameter in Hubbard classic broiler parent stock - Habibullah, M; Hashem, MA; Rana, MS; Islam, MH (Journal of the Bangladesh Agricultural University, 2016)
The experiment was conducted to determine the effect of artificial insemination (AI) on different production parameter in Hubbard Classic Broiler breeder parent stock. A total number of 300 female and 30 male Hubbard Classic broiler breeder parent stock birds were used as experimental animals and parameter recorded are: Health condition and body weight of birds, % of Production, % Hatchability,% Uniformity, grade A chicks, mortality % , hatching egg % & effect of diluents use, birth weight of day old chick (DOC). Significant variation (p<0.01) was observed in number of hatched birds, % of hatchability, production of total no of Grade A chicks, total number of damaged chicks and average chick weight. In the study, hatchability (%), production (%), growth and puberty weight (g) were significantly higher during post insemination compared to pre insemination stage, where as mortality (%) and uniformity (%) were significantly lower in case of post insemination stage. Body weight and uniformity (%) of birds either both sexes were significantly (p<0.01) different in birds at pre insemination stage compared to the birds at insemination. To be mentioned that body weight of birds was negatively correlated to the uniformity. Finally it could be concluded that AI may be better in all the parameters observed in this study than natural mating. So, AI can be practiced in Hubbard Classic broiler breeder parent stock. J. Bangladesh Agril. Univ. 13(1): 71-77, June 2015